Successful hepatectomy for hepatic abscess with chronic granulomatous disease: a case report - Ryo Muranushi; Makoto Suzuki; Kenichiro Araki; Norio Kubo; Sayaka Otake; Yutaka Nishida; Takashi Ishige; Hirokazu Arakawa; Hiroyuki Kuwano; Ken Shirabe (Surgical Case Reports, 2017)
Abstract Background Chronic granulomatous disease (CGD), a rare inherited disorder, is characterized by impaired ability of phagocytic cells to kill certain bacteria and fungi. Although liver abscess is a common manifestation of CGD, its optimal management in these patients is unknown. Here, we present a case of successful hepatectomy for hepatic abscess in a patient with CGD. Case presentation An adolescent patient with previously diagnosed CGD presented to the pediatrics department of our institution with fever. Blood tests showed high concentrations of inflammatory markers. A computed tomography (CT) scan showed a multilocular mass measuring 52 mm × 34 mm in hepatic segment 4 (S4). Blood cultures were negative. Despite administration of antibiotics and γ-globulin, his fever and high concentrations of inflammatory markers persisted and the mass did not change on CT scan images. Because the medications had proved ineffective and percutaneous drainage would have been difficult because of the honeycombing in the abscess, we performed hepatic S4a + S5 anatomic resection and cholecystectomy. Culture of the excised specimen was negative. The patient’s postoperative course was uneventful. On day 62, CT showed no abscess around the resection stump. On day 81, he was transferred to undergo bone marrow transplantation. Conclusions Surgical treatment for hepatic abscess can be effective when medical treatment has failed.